Sustainable livestock systems in Ethiopia: Assessment of the status quo and options for improvement with a focus on animal welfare, market systems, gender roles and human-wildlife conflict management - Sahile, Dagmawit Giref; Justus Liebig University Giessen (My University, 2026)
This study brings together three strands of research to provide a holistic understanding of animal welfare challenges and opportunities in Ethiopia, focusing on farmers' willingness to engage in welfare initiatives, market-level welfare conditions, and traditional methods for managing human-wildlife conflict. Together, these findings offer critical insights for policy and program development aimed at improving both animal well-being and rural livelihoods. The first chapter explores farmers’ preferences and willingness to participate in voluntary animal welfare schemes using mixed logit models in preference and willingness to pay space to assess the relative importance of different attributes of animal welfare schemes on farm households’ participation. Results show that financial incentives are the most significant factor influencing participation. Farmers indicated a need for compensation equivalent to 11% of their annual livestock sales to participate in welfare programs. More demanding welfare improvements such as optimal welfare standards or improved training required significantly higher compensation, up to 25–26% of livestock sales per year. These findings underline the importance of aligning welfare improvements with tangible economic benefits to ensure farmer engagement. Policy recommendations include the development of flexible, farmer-oriented schemes that combine financial incentives with accessible training and community-based approaches. The second chapter assesses the state of animal welfare in three livestock markets: Addis Ababa (terminal), Adama (secondary), and Meki (local). The analysis reveals substantial variation in infrastructure and animal handling practices. While the terminal market offers relatively humane conditions and access to basic amenities such as water and shelter, the local and secondary markets lack such facilities and are characterized by poor handling practices, including forceful movement and lack of rest. These conditions contribute to animal stress and injury, undermining both welfare and market efficiency. Additionally, the study highlights gender inequalities in market participation, with women facing systemic barriers. To address these challenges, the study recommends investment in welfare-supportive infrastructure, implementation of enforceable national welfare standards, comprehensive training for handlers, and policies that actively promote gender inclusion. The third chapter focuses on human-wildlife conflict around Nech Sar National Park, analyzing the economic and social impact of livestock predation and crop damage. Households within 16 kilometers of the park suffer average annual losses of $76.78, which is approximately 77% of their annual income, due to wildlife incursions. While traditional guarding practices are widely used, most respondents viewed them as ineffective unless rigorously applied. Gender differences were also evident: male-headed households experienced greater cattle losses, while female-headed households were more affected by poultry predation which reflects differences between genders in species kept. The findings emphasize the need for a combination of modern and traditional strategies, including expanded buffer zones, improved fencing, gender-sensitive planning, and community engagement to reduce conflict and protect livelihoods. Taken together, these three studies provide a comprehensive picture of the multifaceted issues affecting animal welfare and rural livelihoods in Ethiopia. They underscore the importance of integrating financial incentives, infrastructure investment, gender equity, and local knowledge into national policy. By addressing the economic factors of farmers, improving market conditions, and supporting community-based conservation, Ethiopia can move toward more sustainable and inclusive animal welfare systems.
Keywords: ddc:630; ddc:330